Muskrat Island: Behavioral Shifts of an Insular Muskrat (Ondatra zibethicus) Population in the Gulf of Maine - Alexis M. Mychajliw; Max Zeltsar; John Dennis; Maddie E. Ellms; Dylan Titmuss; Kristen M. Covino; Sara Williams; Shrushti Modi; Courtney A. Hofman (Ecology and Evolution, 2025)
ABSTRACT The aftermath of the North American fur trade resulted in the depletion of many furbearing mammal populations in their native North American range while simultaneously creating invasive populations of these species through translocations worldwide. Here, we document the ongoing results of this mass ecological experiment by describing the natural history of a remnant fur colony of muskrats (Ondatra zibethicus) putatively introduced to the Isles of Shoals archipelago in the Gulf of Maine in the early 20th century. Through a combination of intensive surveys and camera trapping, we document how muskrats have been influenced by insular conditions under expectations of island biogeographic theory. Unlike other translocated muskrats that have produced successful wetland‐restricted populations in continental Europe and Asia, the Shoals muskrats appear to have shifted their habitat use and lodge building behavior and have encountered a new predator: gulls (Laridae). This Nature Note formalizes decades of anecdotal observations and provides important insight into the ecological flexibility of muskrats given the paradox of a species that is apparently now declining in its native range but expanding outside of it.